Design of Driving Waveform Based on Overdriving Voltage for Shortening Response Time in Electrowetting Displays - Zeng, Wenjun; Yi, Zichuan; Zhao, Yiming; Zeng, Weibo; Ma, Simin; Zhou, Xichen; Feng, Haoqiang; Liu, Liming; Shui, Lingling; Zhang, Chongfu; Yang, Jianjun; Zhou, Guofu (Frontiers in Physics, 2021)
A fast response speed of a pixel is important for electrowetting displays (EWDs). However, traditional driving waveforms of EWDs have the disadvantage of long response time. So, a driving waveform, which based on overdriving voltages and charge trapping theory, was proposed in this paper to shorten the response time of EWDs. The driving waveform was composed of an overdriving stage and a driving stage. Firstly, a simplified physical model was introduced to analyze the influence of driving voltages on the response time. Then, an overdriving voltage was applied in the overdriving stage to increase the respond speed of oil, and a target voltage was applied in the driving stage to obtain a target luminance. In addition, the effect of different overdriving voltages and overdriving time values on the response time was analyzed by charge trapping theory to achieve an optimal performance. Finally, the driving waveform was imported into an EWD for performance testing. Experimental results showed that the response time of the EWD can be shortened by 29.27% compared with a PWM driving waveform.